Efektivitas Pendidikan Moral Dalam Pembentukan Karakter Siswa Di TK Islam Terpadu Asa Sumbawa - Ramlafatma, Ramlafatma; Oruh, Shermina; Agustang, Andi (Jurnal Ilmiah Mandala Education (JIME), 2021)
Moral education is a conscious effort to teach the value of goodness including good behavior, in accordance with normative rules and human behavior in daily life. As individual and social beings in society. Moral means costums, habits, values or life procedures, such a honesty, trustworthiness, fairness, responsibility, respect for fellow human beings, harmony, social solidarity and so on which are packaged in the image of goodness. Moral education is very important to shaping the character. Student in moral learning, especially children, need orientation, for example, that treatment become actions or behavior. The purpose of this study was to (1) determine the effectiveness of moral education in student trhough reading daily prayers and short hadiths  in the context of building student character, (2) to know the implementation of moral education methods in student. This type of research is Classroom Action Research or CAR (Classroom Action Research), which is research conducted in a class to find out the consequences of action applied to a research subject in that class. The result of the study show that (1) the educational methods of reading daily prayers and short hadiths in order to shape the character of student is very effective where the abilities possessed by student can show their daily behavior at school. Their morals already reflect Islamic behavior. (2) The learning process carried out by the teacher in collaboration with parents at home is directly interacting with student both during learning and when student are playing.